Measurement and Discrimination of Asymmetric Non-uniform Strain Distribution Based on Spectrum Characterization of FBG Sensors - Fan, Zhichun; Yan, He; Huang, Zhiyong; Liu, Jing (Frontiers in Energy Research, 2022)
The asymmetric deformation of glass-to-metal seals is an important defect that would lead to the failure of the pressure boundary in nuclear reactors. In this research, an efficient approach to measure the asymmetric deformation and prevent the potential failure was proposed based on the spectrum characterization of fiber Bragg grating (FBG) sensors. The asymmetric deformation was induced from small-size large-gradient nonuniform strain in sealing materials; as a result, it could be monitored through the spectra of embedded FBGs affected by strain variations. The theoretical analysis of the FBG spectrum was carried out using the transfer matrix model (TMM) to validate the measuring feasibility and reliability. Based on the theoretical results, the asymmetric deformation was measured by the distributed embedded FBG experimentally. By combining the reconstructed spectrum and the experimental results, the asymmetric deformation of glass-to-metal was proved to be monitored, and the defect was able to be prevented during the manufacturing process effectively via the proposed method.